Comparison between Horizontal and Vertical OFETs by Using Poly (3-Hexylthiophene) (P3HT) as an Active Semiconductor Layer - Mohammed, Bushra H.; Abdullah, Estabraq T. (Iraqi Journal of Science, 2020)
In this paper, a comparison between horizontal and vertical OFET of Poly (3-Hexylthiophene) (P3HT) as an active semiconductor layer (p-type) was studied by using two different gate insulators (ZrO2 and PVA). The electrical performance output (Id-Vd) and transfer (Id-Vg) characteristics were investigated using the gradual-channel approximation model. The device shows a typical output curve of a field-effect transistor (FET). The analysis of electrical characterization was performed in order to investigate the source-drain voltage (Vd) dependent current and the effects of gate dielectric on the electrical performance of the OFET. This work also considered the effects of the capacitance semiconductor on the performance OFETs. The values of current, as calculated using MATLAB simulation, exhibited an increase with increasing source-drain voltage. Also, the organic transistor modeling software was used to evaluate the transconductance calculated. The best results for the vertical OFET were achieved using the gate insulators of ZrO2.